EFEKTIFITAS ITSBAT NIKAH PASCA DIBERLAKUKANNYA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI PENGADILAN AGAMA - Fauzi, Rahmat; Pasmatuti, Darda (Ensiklopedia Sosial Review, 2019)
Itsbat Nikah is a process of Marriage Registration for a marriage that has been carried out in Islam. Marriage registration is carried out in order to obtain a marriage certificate as proof of the validity of the marriage that has been done. The purpose of this research is to find out and analyze the effectiveness of marriage law after the enactment of Law Number 1 of 1974 in the Religious Courts from a juridical analysis perspective. The results of the analysis of research data on the rule of law are complete starting from the mandate of the Act. The main obstacle for the Religious Courts to be able to carry out their functions optimally in carrying out marriages against unregistered marriages is that there is no strong legal umbrella.